ANALISIS HUBUNGAN PERDAGANGAN, INVESTASI ASING DAN PERTUMBUHAN EKONOMI DI INDONESIA - Liasulistia Ningsih; Indra Ismayudi Tanjung; Hartini; Puput Arisna (Universitas Pasundan, 2025)
Globalization has significantly contributed to economic growth through trade liberalization, technological advancement, and international cooperation. In Indonesia, trade openness and foreign direct investment (FDI) serve as crucial drivers of economic growth, primarily through exports, imports, and technology transfer. However, the relationship between trade, investment, and economic growth is not always linear, as it is shaped by a country’s internal characteristics and economic policies. This study aims to examine both the short-run and long-run relationships among trade, FDI, and economic growth in Indonesia using annual data from 1970 to 2024 and applying the Vector Error Correction Model (VECM) approach. The findings reveal that, based on the Impulse Response Function (IRF) analysis, each variable tends to stabilize in response to shocks from itself or other variables in the long run. In the short run, trade and FDI respond positively only to shocks in economic growth, while economic growth increases primarily due to shocks from FDI and trade. Furthermore, the Variance Decomposition (VD) analysis indicates that the most dominant influence on the variability of trade, FDI, and economic growth comes from each respective variable itself. These results highlight the dynamic interdependence among trade, investment, and economic growth, offering valuable insights for policymakers in formulating strategies to enhance Indonesia’s long-term economic performance